2006
DOI: 10.1111/j.1365-2648.2006.03873.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and physical self‐concept: comparison between children with and without asthma

Abstract: Asthma interferes with children's ability to participate in vigorous physical activity but not in moderate-to-vigorous physical activity. Gender determines primary differences in physical self-concept. Appropriate exercise recommendations are necessary to encourage children with asthma to engage in vigorous physical activity for normal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
5
44
1
2
Order By: Relevance
“…Objective recording may though be more adequate to capture actual PA (8). However, differences in moderate to vigorous physical activity (MVPA) are not evident in either of the studies (6,7), which is confirmed in a Norwegian cohort (9), of which this study depends on. Furthermore, van Gent et al (10) did not found lower level of VPA based on both self-reports and objective recordings, and neither did Nystad (11) at any level of exercise frequency or exercise hours a week in asthma based on self-reports.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Objective recording may though be more adequate to capture actual PA (8). However, differences in moderate to vigorous physical activity (MVPA) are not evident in either of the studies (6,7), which is confirmed in a Norwegian cohort (9), of which this study depends on. Furthermore, van Gent et al (10) did not found lower level of VPA based on both self-reports and objective recordings, and neither did Nystad (11) at any level of exercise frequency or exercise hours a week in asthma based on self-reports.…”
Section: Introductionsupporting
confidence: 50%
“…A similar distinction is reported in children with asthma overall by self-reported VPA (7). Objective recording may though be more adequate to capture actual PA (8).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…One explanation may be that asthmatic adolescents in Sweden are relatively well treated, which implies that they can participate in physical education with little or no restrictions. In line with earlier research (Chiang et al., 2006), asthmatic girls in our study participated to a lesser extent in physical education than asthmatic boys. However, the idea that asthma is the cause of the girls’ reduced participation should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 77%
“…There is an ongoing discussion on whether or not the level of physical activity differs between asthmatic children and their healthy peers. Some researchers argue that there is no difference in physical activity level (Nystad, Nafstad, & Harris, 2001) while others claim that asthma interferes with children's ability to participate in vigorous physical activities (Chiang, Huang, & Fu, 2006). However, children with asthma report that running, bicycling, playing football and physical education are activities that are restricted due to their illness (Rydström et al., 2005).…”
Section: Introductionmentioning
confidence: 99%